2019
DOI: 10.1038/s41594-019-0193-2
|View full text |Cite|
|
Sign up to set email alerts
|

A gel phase promotes condensation of liquid P granules in Caenorhabditis elegans embryos

Abstract: RNA granules are sub-cellular compartments proposed to form by liquid-liquid phase separation (LLPS), a thermodynamic process that partitions molecules between dilute and condensed liquid phases. The mechanisms that localize liquid phases in cells, however, are not fully understood. P granules are RNA granules that form in the posterior of C. elegans embryos. Theoretical studies have suggested that spontaneous LLPS of the RNA-binding protein PGL-3 with RNA drives P granule assembly. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
261
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(282 citation statements)
references
References 33 publications
21
261
0
Order By: Relevance
“…We suggest that germ granules are not crucial for RNAi per se, but rather are important for small RNA homeostasis, with consequences that can persist for multiple generations. Previous studies have shown that the stability of the germ granules is affected by environmental changes (for instance temperature 55,56 ), and also that temperature shifts trigger changes in heritable small RNAs 3,57 . Because germ granules impact small RNA biogenesis, the granules could be important mediators in the translation of environmental changes to small RNA-mediated transgenerational memory.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that germ granules are not crucial for RNAi per se, but rather are important for small RNA homeostasis, with consequences that can persist for multiple generations. Previous studies have shown that the stability of the germ granules is affected by environmental changes (for instance temperature 55,56 ), and also that temperature shifts trigger changes in heritable small RNAs 3,57 . Because germ granules impact small RNA biogenesis, the granules could be important mediators in the translation of environmental changes to small RNA-mediated transgenerational memory.…”
Section: Discussionmentioning
confidence: 99%
“…MEG-3 and MEG-4 form gel-like scaffolds that recruit and stimulate the coalescence 67 of P granule proteins in germ plasm to ensure their partitioning to the embryonic germline and the 68 primordial germ cells Z2 and Z3 (Fig. 1;Putnam et al, 2019). In meg-3 meg-4 embryos, P granules do not 69 coalesce in germ plasm, causing granule components to be partitioned equally to all cells and turned 70 over ( Fig.…”
mentioning
confidence: 99%
“…Their liquid-like property is thought to facilitate dynamic internal rearrangements as well as exchange of materials with their surroundings. However, recently a non-dynamic, gel-like scaffold has been found to envelope the liquid-core of P granules (Putnam et al, 2019). Moreover, differences in translational activity between the periphery and the core of the P-bodies have been observed in Drosophila oocytes (Weil et al, 2012).…”
Section: Deps-1 and Prg-1 Ultrastructurementioning
confidence: 99%